India’s Blueprint for Sustainable Growth - Jain, Harshita; Rajak , Vaibhav (Trinity Law Review, 2025)
This article analyses India’s strategy for attaining sustainable prosperity by 2047, in  line with its aspiration to become a developed nation by the 100th anniversary of its  independence. It addresses the challenges arising from swift urbanization, industrial  growth, and increasing energy requirements, detailing how the Indian government  has enacted measures such as the National Action Plan on Climate Change (NAPCC)  to tackle these issues. The analysis underscores India’s dedication to minimizing  its ecological footprint while promoting economic advancement through clean  energy initiatives, technological progress, and infrastructure enhancement. Notable  programs like Make in India, Digital India, and Atmanirbhar Bharat are designed to  boost domestic manufacturing and self-reliance while fostering sustainability. The  vision of Viksit Bharat (Developed India) prioritizes human capital development,  the adoption of renewable energy, and international partnerships to achieve net zero emissions by 2070 and to derive 50% of energy from renewable sources by  2030. Furthermore, the document investigates the crucial contributions of green  energy, digital innovation, and global collaborations in promoting sustainability. By  implementing these cohesive strategies, India seeks to harmonize economic growth,  environmental responsibility, and social equity, positioning itself as a frontrunner  in sustainable development. This holistic approach aims to secure a resilient and  sustainable future for India while supporting global environmental objectives.
Keywords: analyses; infrastruc ture; equity; social; emission